Associations of muscle size and fatty infiltration with bone mineral density of the proximal femur bone - Li, Junfei; Wang, Yijing; Zhang, Xuesong; Zhang, Ping; Su, Yunshan; Bai, Lin; Wang, Yali; Wang, Ming; Zhao, Jian (Frontiers in Endocrinology, 2022)
Purpose: To investigate the relationship of muscle atrophy and fat infiltration around the hip joint with areal bone mineral density (aBMD) in each subregion of the proximal femur.Materials and Methods: 144 participants (66 women and 78 men) were examined by quantitative computed tomography (QCT), and areal bone mineral density (aBMD) of the femoral neck (FN), trochanter (TR), and intertrochanter (IT) of the proximal femur were obtained. The cross-sectional area (CSA) and proton density fat fraction (PDFF) of the gluteus maximus (G.MaxM), gluteus medius (G.MedM), gluteus minimus (G.MinM), and iliopsoas (IliopM) were obtained via magnetic resonance imaging (MRI) using the mDIXON-Quant sequence. A multivariate generalized linear model was used to evaluate the correlation of the CSA and PDFF of muscles with aBMD in all subregions of the proximal femur.Results: The FN integral (Int) aBMD was significantly associated with the G.MaxM CSA (men: P = 0.002; women: P = 0.008) and PDFF (men: P ˂ 0.001; women: P = 0.047). Some muscle indexes were related to the FN aBMD in males or females, including the CSA of G.MedM, G.MinM, and IliopM as well as the PDFF of IliopM and G.MinM. Associations of hip muscle parameters with the TR Int aBMD in both males and females were observed, including G.MaxM CSA (men: P < 0.001; women: P = 0.028) and G.MaxM PDFF (men: P = 0.031; women: P = 0.038). Other muscle indexes, including G.MedM and IliopM, were related to the TR aBMD, mainly affecting the aBMD of TR cortical (Cort) and TR Int. The IT Int aBMD and IT Cort aBMD showed significant correlation with the muscle indexes of G. MaxM, IliopM, and G.MedM, including the PDFF and CSA in males and females. Further, more indicators of the G.MedM and IliopM correlated with the TR and IT aBMD compared to the FN aBMD.Conclusions: The CSA of gluteus muscles and iliopsoas had a positive association with the aBMD in the proximal femur, and the PDFF had a negative correlation with the aBMD. In addition, there was an interaction of the proximal femur aBMD with the muscle size and fatty infiltration of hip muscles.